Let's simplify the original expression step by step:
The expression is: \[ \frac{1}{2}(9 - 70) + (-29)0 \]
First, calculate \( (-29)0 \): \[ (-29)0 = 0 \] So the expression simplifies to: \[ \frac{1}{2}(9 - 70) + 0 = \frac{1}{2}(9 - 70) \]
Next, calculate \( 9 - 70 \): \[ 9 - 70 = -61 \]
Now, substitute this back into the expression: \[ \frac{1}{2}(-61) \] This simplifies to: \[ -\frac{61}{2} \]
Now let's check which of the given options is equivalent to \(-\frac{61}{2}\):
-
Option 1: \(\frac{1}{2}(9 - 1) + 1 = \frac{1}{2}(8) + 1 = 4 + 1 = 5\)
-
Option 2: \(\frac{1}{2}(9 - 0) + 0 = \frac{1}{2}(9) + 0 = \frac{9}{2}\)
-
Option 3: \(\frac{1}{2}(2) + 1 = 1 + 1 = 2\)
-
Option 4: \(\frac{1}{2}(9 - 1) - 1 = \frac{1}{2}(8) - 1 = 4 - 1 = 3\)
None of the options given are equal to \(-\frac{61}{2}\).
Thus, there seems to be no equivalent expression among the choices provided.